Factors Affecting Result in Chinese Proficiency Test (HSK) Level 6: Reading Section and Preparation Strategies - Sri Haryanti (Bina Nusantara University, 2013)
Chinese Proficiency Test (HSK) is an internationally standardized exam which tests and rates Chinese language proficiency. The highest level in this test is level 6. The writing part of the test consists of 3 (three) parts, namely, (1) listening, (2) reading, (3) writing. Furthermore, the reading part is made of 4 components. Level 6 of this test implies a high degree of difficulty. This paper specifically looked on how to prepare effectively for participants to be able to work on the reading part in order to achieve best result. This article used the methods of literature review and observational study as well as field research and would also incorporate the author’s personal experience in taking the test into recommending strategies for doing the reading part in a level 6 HSK test. Finally, research suggested several techniques and tips that might assist participants in achieving maximum scores in handling the reading part of level 6 HSK test.